(3JaUjd YbO GdaQGFO HJcejd bjO GdTQGFOs - (3CHh GdHQcGJ YHO GdHQ Hf eMeO Hf eMeO, SQj GdOjf , GHf GdTMfI,J (B921 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eMce GdTQY GdMfja heDjOg, hQGaY GdePgH GdMfja SjOfG eMeO heSOOg, hgGOjg Edi GdUQGW GdeSJbje heQTOg s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf GdPi HfYeJg JJe GdUGdMGJ hJfRd GdHQcGJ hJRhd GdVQhQGJ MeOG jhGai fYeg , hjcGaF eRjOg, hjOaY fbeg s
(3GdfU TQM defXheI bjO GdTQGFO hfXe GdaQGFO dGHf hgHGf J (B768 (3g`s
(3hgj bUjOI QGFjI ef HMQ GdWhjds
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1865s
Keywords: (3Gdabg GdMfajs